Efficient regeneration of mature castanopsis hystrix from in vitro stem explants - Zhang, Heng; Guo, Mengqing; Wu, Qiaona; Zhao, Mengqiu; Li, Ruiping; Deng, Xiaomei; Xi, Ruchun (Frontiers in Plant Science, 2022)
Castanopsis hystrix is one of the main timber trees grown in China. However, severe shortage of natural seeds and the difficulty of explant regeneration has limited seedling supply. As such, there is a need for research on asexual multiplication of C. hystrix. This study established a rapid propagation technology system for C. hystrix genotypes, including explant treatment, proliferation, and rooting. HZ (a modified MS medium) supplemented with 4.4 µM BA and 0.5 µM IBA was found to be the optimal medium for shoot sprouting. The maximum proliferation coefficient and the number of effective shoots was obtained on HZ medium supplemented with 2.6 µM BA and 1.0 µM IBA, were 3.00 and 5.63, respectively. A rooting rate of 83.33% was achieved using half-strength HZ medium supplemented with 3.2 µM NAA. Adding vitamin C (80 mg·l-1) for seven days in a dark environment reduced the browning rate, while increasing the proliferation rate. Additionally, through cytological observation, we established how and where adventitious roots occur. The survival rate of transplanted plantlets was >90%. This is the first report of an in vitro regeneration technique that uses stem segments of mature C. hystrix as explants.